Artificial Intelligence and Social-Emotional Learning: what relationship? - Rosa Indellicato (Journal of Modern Science)
Objectives Among the skills included in the Compass for Tomorrow are new skills for teachers and educators in the context of emotional artificial intelligence. Is it possible to teach social-emotional skills? And how is it possible to do so? Can socio-emotional competences be considered as curricular standards? This contribution aims to answer these questions, highlighting opportunities and risks that the digital revolution and affective computing pose today.